1997
DOI: 10.1523/jneurosci.17-14-05380.1997
|View full text |Cite
|
Sign up to set email alerts
|

A Novel Type of GABAergic Interneuron Connecting the Input and the Output Regions of the Hippocampus

Abstract: The main excitatory pathway of the hippocampal formation is controlled by a network of morphologically distinct populations of GABAergic interneurons. Here we describe a novel type of GABAergic interneuron located in the outer molecular layer (OML) of the rat dentate gyrus with a long-range forward projection from the dentate gyrus to the subiculum across the hippocampal fissure. OML interneurons were recorded in hippocampal slices by using the whole-cell patch-clamp configuration. During recording, cells were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
55
0
1

Year Published

1999
1999
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 76 publications
(59 citation statements)
references
References 57 publications
3
55
0
1
Order By: Relevance
“…Because the rabies virus completely fills the axons and dendrites of infected neurons with mCherry, it allows us to visualize the detailed morphology of MOPP cells. Outer molecular layer (OML) cells were another cell type found in the MLs in the rat, which had axons that projected across the hippocampal fissure toward the subiculum area (23). It is unlikely that OML cells were labeled because we found that the rabies virus only labeled cells that strictly confined their axons to the ML and we did not see mCherry-labeled axons or cell bodies in the subiculum (Fig.…”
Section: Resultsmentioning
confidence: 77%
“…Because the rabies virus completely fills the axons and dendrites of infected neurons with mCherry, it allows us to visualize the detailed morphology of MOPP cells. Outer molecular layer (OML) cells were another cell type found in the MLs in the rat, which had axons that projected across the hippocampal fissure toward the subiculum area (23). It is unlikely that OML cells were labeled because we found that the rabies virus only labeled cells that strictly confined their axons to the ML and we did not see mCherry-labeled axons or cell bodies in the subiculum (Fig.…”
Section: Resultsmentioning
confidence: 77%
“…Amplicons were analyzed by agarose gel electrophoresis using ethidium bromide fluorescence. Oligonucleotide primers were derived from unique sequences to specifically amplify individual NR2 subunits (Porter et al, 1998), the 67-kDa form of glutamic acid decarboxylase (Ceranik et al, 1997), or GAPDH (Salazar et al, 1999). All oligonucleotides were obtained from commercial sources (Sigma Genosys, The Woodlands, TX).…”
Section: Methodsmentioning
confidence: 99%
“…Interneurons have been reported with axonal arborization not respecting hippocampal areal boundaries, including the so-called CA1 backprojection cell innervating the CA3 area and the dentate gyrus (Sik et al, 1994), the perforant path associated cells innervating CA1 and subicular pyramidal cells and dentate granule cells (Ceranik et al, 1997;Vida et al, 1998;Klausberger et al, 2005), and the hippocamposubicular cells in the mouse (Losonczy et al, 2002). Overall, at least seven types of GABAergic projection neurons exist in the CA1 area.…”
Section: Diversity Of Gabaergic Projection Cell Typesmentioning
confidence: 99%
“…For example, hippocampal GABAergic neurons innervate the medial septum (Alonso and Kohler, 1982) and commissural GABAergic cells interconnect the dentate gyri (Ribak et al, 1986;Leranth and Frotscher, 1987). Other interareal connections include the projection from the presubiculum to the entorhinal cortex (van Haeften et al, 1997) and interregional connections of hippocampal fields (Sik et al, 1994(Sik et al, , 1995Ceranik et al, 1997;Losonczy et al, 2002;Gulyas et al, 2003;Ferraguti et al, 2005). Long-range GABAergic projections have also been described in the isocortex (Gonchar et al, 1995;Manzoni, 1996, 2004;Jinno and Kosaka, 2004;Tomioka et al, 2005).…”
Section: Introductionmentioning
confidence: 99%